Development of electricarc pseudoalloy coatings for the strengthening of copper walls of molds - Borisov, Yuri; Vigilianska, Nataliia; Demianov, Ivan; Grishchenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2018)
On the basis of the requirements for protective coatings of molds, the materials of pseudoalloys were determined for applying coatings from two wires. One of the wires is copper, which provides maintaining a sufficient thermal conductivity of the layer, and the second one consists of a material, which provides wear resistance of a coating. As the second wire, the wires NiCr, Mo, Ti and a flux-cored wire were used, consisting of a steel sheath and a filler – FeB powder. Based on the calculation data on the thermal conductivity of coatings, taking into account the coefficients of heat transfer, the estimation of the influence of these coatings on the thermal processes in the mold (temperature of the wall surface, intensity of heat removal from the wall) was performed. Applying electric-arc spraying, the pseudoalloy coatings with a uniform distribution of components were produced, one of which is copper with a hardness of 1,320–1,460 MPa, and the second one is the strengthening component NiCr, with a hardness of 2,440 MPa; Mo, with a hardness of 5,350 MPa; Ti, with a hardness of 7,540 MPa; FeB, with a hardness of 7,050 MPa. As a result of measurements of the coefficient of thermal expansion of coatings, it was found that the coating Cu-NiCr is the closest to the coefficient of thermal expansion of copper. Then it is followed by Cu-FCW (FeB), Cu-Ti and Cu-Mo. The abrasive wear resistance of pseudoalloy coatings at a room temperature exceeds pure copper 1.4–2.3 times. The tests of pseudoalloy coatings for resistance to wear during heating to 350 °C showed that the wear resistance of Cu-NiCr and Cu-FCW (FeB) coatings exceeds the resistance of pure copper 4.5 and 22 times, respectively. The hot hardness of the coating Cu-NiCr in the range of 20–400 °C exceeds the hardness of pure copper 3 times.